Comparison of Nanopore Structure Evolution in Vitrinite and Inertinite of Tectonically Deformed Coals: A Case Study in the Wutongzhuang Coal Mine of Hebei Province, North China - Wang, Anmin; Li, Jing; Cao, Daiyong; Wei, Yingchun; Ding, Liqi; Zhao, Meng (Frontiers in Earth Science, 2022)
The understanding of the nanopore structure in tectonically deformed coal (TDC) could be expanded from the perspective of a single maceral. A total of 10 TDCs with an increasing deformation degree (in the order of unaltered, cataclastic, porphyroclast, scaly, and powdery coal), were collected in a single coal seam and stripped into 10 vitrinite and 10 inertinite samples. Carbon dioxide (CO2) adsorption and nitrogen (N2) adsorption / desorption experiments were conducted to reveal the nanopore structure, whereas 13C solid-state nuclear magnetic resonance and X-ray diffraction experiments were conducted to detect the macromolecular structure. The results reveal that the macromolecular structures of both vitrinite and inertinite can be altered by tectonic stress. As the deformation degree increases, the aliphatic carbons decrease, the aromatic carbons increase, and the aromatic interlayer spacing decreases, whereas the crystallite stacking height and the average number of crystallites in a stack increase. For mesopores, the pore volume of vitrinite slowly decreases and then increases at the stage of scaly coal, whereas that of inertinite fluctuates with no obvious regularities. For micropores, the pore volume of vitrinite deceases as the deformation degree increases, whereas that of inertinite decreases since the deformation stage of porphyroclast coal, and little changed from the deformation stage of unaltered to cataclastic coal. As the coal deformation degree increases, the aromatic interlayer spacing decreases, resulting in a decrease in the micropore volume; however, the average crystallite stacking height and the average number of crystallites in a stack increase, leading to an increase in the micropore volume. Therefore, the micropore decreases and then increases as the coal deformation degree increases. However, the macromolecular changes weakly affect the mesopore evolution in the coal deformation process.